Theacher' Role in Implementing Occupational Therapy in Chlidren Aged 5-6 Years with Motor Sensoric Disorders - Ari Iswati; SEPTIYANI ENDANG YUNITA SARI; Ana Mariana; Babay Nurbani; Naili Faizah; Sofhia Aesti (Universitas Panca Sakti Bekasi, 2023)
The purpose of this study was to examine or see the teacher's role in the application of occupation to sensorimotor development in children aged 5-6 years. The problem in this study, namely how is the implementation of occupational therapy carried out by the teacher, what are the goals of occupational therapy and how is the influence of the development of occupational therapy carried out at TKI Al Azhar 1 Jakarta. The research method used is qualitative, namely by using a descriptive analytic method, namely by describing and analyzing the subject matter. Data collection techniques through observation, interviews and documentation studies. The results showed that there was an increase in the sensorimotor abilities of DF children as indicated by increased pinching and grabbing abilities, being able to hold a writing instrument, being able to draw vertical, horizontal and diagonal lines, and having the ability to do cutting activities. Occupational therapy greatly influences the sensorimotor development of Early Childhood.